Study on Positron Annihilation Rate in Water - Nghiep, Tran Dai (Communications in Physics, 2008)
Measurement system for determination of positron annihilation rate is consisted of HPGe detector, multichannel analyser and Na$^{22}$ positron source. The result of annihilation rate measurement in wetted filter paper is treated. The formula of energy transfer model is used for explanation obtained data quantitatively.